The Role of Motor Imagery in Predicting Motor Skills in Young Male Soccer Players - Dariusz Zapała (International Journal of Environmental Research and Public Health, 2021)
The study aimed to find out whether the imagery ability within the two subcomponents of motor imagery (visual and kinesthetic) allows predicting the results in simple response time task and eye–hand coordination task in a group of young male soccer players (9–15 years old). Non-specific simple response time and eye–hand coordination play a key role in predicting specific sports performance level. Participants performed Reaction Time Task, Eye–Hand Coordination Task, and completed Motor Imagery Questionnaire–Revised. Data were submitted to the structural equations analysis based on the maximum likelihood method in order to estimate a structural model of relationship between variables. Results indicate visual rather than kinesthetic motor imagery is associated with non-specific motor skills. Higher scores on the visual motor imagery scale were observed to correlate with faster reaction times and better coordination in the study group. This supports the idea that during learning a new perceptual-motor-task the visual control is required. Results provide the evidence for the specific role of the third-person perspective imagery in young athletes playing soccer.